A Radical Solution to the Race Problem. Issue 5 (December 2014) - Spencer, Quayshawn
Abstract : It has become customary among philosophers and biologists to claim that folk racial classification has no biological basis. This paper attempts to debunk that view. In this paper I show that 'race', as used in current US race talk, picks out a biologically real entity. I do this by first showing that 'race', in this use, is not a kind term, but a proper name for a set of human population groups. Next, using recent human genetic clustering results, I show that this set of human population groups is a partition of human populations that I call 'the Blumenbach partition'.